2020
DOI: 10.3390/ijerph17197352
|View full text |Cite
|
Sign up to set email alerts
|

Risk Information Seeking Behavior in Disaster Resettlement: A Case Study of Ankang City, China

Abstract: In 2011, the Chinese government launched a disaster mitigation and preparedness program called the Resettlement of South Shaanxi (RSS). Due to the wide geographical scope and complex interests, the possibility of conflicts was increased during and after resettlement. Efficient risk communication improves the supply of information about risks and meets the risk-related information needs of individuals. Using the risk information seeking and processing (RISP) model, this research applied a structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(87 reference statements)
0
8
0
1
Order By: Relevance
“…Academic research on human urbanization covers many fields, but traditional studies have focused on the household registration (hukou) system and the urban status of migrant people [ 16 ]. In recent years, the issue of human cognitive differences has also gradually gained attention [ 17 ]; for example, public health service utilization [ 18 ], educational assortative mating in marriage [ 19 ], and risk information-seeking behavior [ 20 ]. Through a literature review, this study found that elderly migrants reflect various cognitive characteristics of production and living needs.…”
Section: Literature Review and Research Methodsmentioning
confidence: 99%
“…Academic research on human urbanization covers many fields, but traditional studies have focused on the household registration (hukou) system and the urban status of migrant people [ 16 ]. In recent years, the issue of human cognitive differences has also gradually gained attention [ 17 ]; for example, public health service utilization [ 18 ], educational assortative mating in marriage [ 19 ], and risk information-seeking behavior [ 20 ]. Through a literature review, this study found that elderly migrants reflect various cognitive characteristics of production and living needs.…”
Section: Literature Review and Research Methodsmentioning
confidence: 99%
“…Berkaca dari pengalaman sebelumnya, bahwa banyaknya jumlah korban bencana alam yang terjadi di Banda Aceh diakibatkan karena para korban tidak mempunyai pengetahuan tentang ancaman gempa dan tsunami yang dapat terjadi (Febriana, Sugiyanto, & Abubakar, 2015). Hal ini sejalan dengan sebuah penelitian tentang kurangnya pengetahuan tentang potensi bencana dapat menyebabkan rendahnya kesiapsiagaan saat bencana terjadi (Shi, Hu, Guo, & Lian, 2020).…”
Section: Berdasarkanunclassified
“…• disease risk (Trumbo, 1999;Trumbo, 2002;Etchegary and Perrier, 2007), • computer and information technology (Winter, 2020;Zhang and Skoric, 2020), • information security (Luo et al, 2013;Frauenstein and Flowerday, 2020), • food safety (Kim and Paek, 2009;Chen, 2016), • crisis management (Shi et al, 2020), • decision-making (Allison et al, 1990) • marketing field (Zhang et al, 2014;Lanero et al, 2020).…”
Section: The Heuristic-systematic Model Of Information Processingmentioning
confidence: 99%
“…Extant research also centers on the heuristic cues. As results suggest, consumers' heuristic processing can be activated through the sequence of positive and negative information (Ruiz-Mafe et al, 2018), time pressure (Bigne et al, 2021), rate of hotel rooms (Luo et al, 2021), social influence (Shi et al, 2020), website design (Kim et al, 2017), recommender identity disclosure (Li and Yang, 2017) and cost savings (Lee and Chung, 2019) and can further promote consumers' likeliness to purchase.…”
Section: The Heuristic-systematic Model Of Information Processingmentioning
confidence: 99%